Open Source Hardware for Human Development - Herrera, Alfredo (Université d'Ottawa / University of Ottawa, 2015)
Human Development is not a term used in casual conversation, it describes the current approach used by large aide international development organizations like the United Nations; but most people are familiar with the terms “emergency relief” and “humanitarian intervention”. Emergency relief focuses on providing assistance to save lives, alleviate suffering, or protect populations; while human development uses various societal levers to improve living conditions. The United Nation has been publishing an annual report on human development since 1990 (UNDP 1990), and it is widely recognized as a consistent measure of global living conditions. Development strategies revolve around a transfer of something valuable to an aided population: education, vaccination, fertilizers, etc. In technology-based human development projects, technology artefacts (a medical record computer system, solar electrification systems, irrigation) and related knowledge (education, operation and maintenance instruction) are those valuables being transferred. The benefits of technology are specific to each economy, and dependant on how quickly technology is adapted and integrated in the local economy (Cypher & Dietz 2008). The value of ideas increases to the degree they can be shared with and used by others (Houghton & Sheehan 2000): the more knowledge is diffused and adopted, the greater its value. The success of free and open-source software exemplifies this principle, and a growing number of scholars agree that the model also applies to hardware (Balka et al. 2009; Thompson 2008). This thesis presents research on open source hardware and its knowledge-sharing approach as a means to human development. It presents a model that leverages the collaborative design methodology of open hardware for adoption of artefacts that address pressing “humanitarian technology” needs, for example, in health or education. To achieve this, critical literature reviews on open source and on technology-based human development are first done; the findings from literature are then complemented with the findings from interviews and case studies to model a sustainable deployment strategy for open source use in human development projects. Adopting the human development paradigm defined in the first Human Development Report (“HDR1990”), which aims at three people-centered aspirations: to live a long and healthy life, to be educated and to have access to resources needed for a decent standard of living (UNDP 1990). This thesis research models its deployment strategy using the Soft Systems Methodology (SSM), showing that: (a) open source hardware, like any technology used in development, can magnify effective development programs when used appropriately; (b) Dr. E.F. Schumacher’s appropriate technology principles, and P. Polak’s reinstatement, mesh very well with the open source methodology, as long as required constituents in the aided communities are taken care of (availability of electricity, internet access, technical know-how, etc.); (c) extreme affordability is particularly important for open source hardware, because a sustainable strategy is based on the belief that aided population would want to procure these artifacts if they improve their earning potential; (d) participatory human development practices work well with the open source methodology, but “solutions” must be fully verified before deployment. This document is structured in 5 chapters: introduction, literature review, research strategies, case studies and interviews, and conclusion. The appendix include three articles published on parallel work for the Institute of Electrical and Electronic Engineers (IEEE) on defining a strategy for the IEEE’s use of opens source technology in their humanitarian activities. This research provides insight into the new topic of open source hardware and its proposed use in the mission critical context of international development; because entrepreneurship is a key enabler to the strategy it describes, I hope the research can support future work on that aspect.
Keywords: open source hardware; human development; economic development; soft systems methodology; open source; complex system; appropriate technology; deployment strategy